Polska tolerancja czy początki oświecenia? Jonasz Szlichtyng (1592‑1661) jako teolog „drugiej reformacji” - Ptaszyński, Maciej (Odrodzenie i Reformacja w Polsce, 2013)
Polish Toleration or the Beginning of the Enlightenment? Jonasz Szlichtyng (1592‑1661) as Theologian of the second Reformation The article deals with socianian theologian, Jonasz Szlichtyng (Jonas Schlichting), who was the main pastor in Raków, the centre of socinians (called the Polish Brethren), in the times when they suffered the hardest persecutions which led to their expulsion from Poland in 1658. His exegetical works, reprinted in the Bibliotheca Fratrum Polonorum, were very popular among the intellectuals on the eve of the Enlightenment. The historiography interpreted the change of the attitude towards the Polish Brethren in terms of the transition from the religious toleration of the 16th century towards the persecutions and intolerance of the 17th century. The Brethren were perceived either as successor of the ideas of toleration and a cradle of the Enlightenment, or a traitor of the “Polish nation”. In the essay, these general theses are repudiated upon the analysis of the Szlichtyng’s thought. The author focused on Trinitology, Christology, Soteriology, and Szlichtyng’s attitude towards the secular and ecclesiastical authorities. The reconstruction is based on Szlichtyng’s polemics and some of his exegetical writings. According to the author, Szlichtyng was a typical theologian of the “second reformation” who stressed the role of the piety and a need for change of believers’ lifestyle. By demonstrating the evolution of Szlichtyng’s opinions in the eve of Colloquium Charitativum (Toruń, 1645), the author claims that Szlichtyng made an effort to bring the Brethren closer to other protestant confessions. The author argues that Szlichtyng attempted to reconcile the socinians with the Calvinists. The efforts of Szlichtyng as well as the banishment of Brethren belonged to the process of the confessional development of 17th century, comparable with evolution of other religious communities in Europe.